The persuasive leader : lessons from the arts - Carroll, Stephen J., 1930-; Flood, Patrick C. (San Francisco : Jossey-Bass, 2010)
The communication aspect of leadership - to actively engage your followers and achieve understanding and motivation whilst making the message memorable - has never been more important. Using vivid lessons and examples from spheres outside business organization, The Persuasive Leader explores the leader's role as a communicator and teaches the fundamental principles of successful leadership. This book provides insights and principles about persuasive leadership from a broad range of human experiences. It draws on examples of persuasive leaders and persuasive leadership principles from the perfo.
Persuasive leadership in life and work -- Using aesthetics and the arts in persuasive leadership -- Using words effectively in persuasive speech and writing -- Persuasive leadership and rhetoric principles -- Persuasive leadership-planning considerations -- Audience characteristics -- Leader-follower emotional ties -- Creating positive responses in sub-leaders and followers -- Persuasive leadership and change -- Strategic plans as a persuasive tool -- Harmful persuasion -- Self-leadership -- Persuasive variations in different settings -- Achieving trust and cooperation -- The noble persuasive leader -- Leadership emergence -- Handling problems and failure -- Why become a persuasive leader?
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Leadership; Persuasion (Psychology) in organizations; Communication in management; Leadership; Communication en gestion; POLITICAL SCIENCE -- Political Process -- Leadership; Communication in management; Leadership; Persuasion (Psychology) in organizations